(Dis)unity in the Archaic monetary systems of the western Chalkidian Apoikiai - van Alfen, Peter (Journal of Greek Archaeology, 2020)
The first coins in the Mediterranean world were struck by a number of Lydian and Greek rulers in western Asia Minor sometime around the middle of the 7th century BC in electrum, a manmade alloy of gold and silver. Roughly a century later, around 540-30 BC, poleis in Asia Minor, the Greek mainland, and in the western Mediterranean began to strike coins predominantly in silver; by the end of the 6th century BC hundreds of poleis were producing silver coins. Among the earliest producers of silver coinage were the northern Aegean apoikiai (‘colonies’) of the Euboian poleis of Chalkis and Eretria as well as the metropoleis (‘mother-cities’) themselves, all of which began to strike coins sometime around the third quarter of the 6th century. The monetary connections between the northern apoikiai and the cities of Euboia included not just a shared weight standard and denominational structure, but also, in the case of Eretria and Karystos on Euboia and the apoikia Dikaia in the Chalkidike, shared numismatic iconography; the coins of these three poleis are so similar that attribution to one or the other is sometimes difficult (Figures 1–5). Common to all three was the cow with its head reversed on the obverse, while on the reverse of the coins there was either a sepia (cuttlefish) (Eretria, Dikaia) or a cockerel (Karystos, Dikaia), which also appeared as an obverse type on smaller denominations of Dikaia (Figure 4). Significantly, Chalkis on Euboia did not share iconography with these three cities, although the coins of Chalkis did share a similar denominational structure and weight standard with the others. Were such similarities in iconography and monetary attributes simply a case of imitation, a not uncommon occurrence among ancient coin producers, or a sign of more significant economic, political, or social relationships?